Variation of growth in the production of the BCG vaccine and the association with the immune response. An observational study within a randomised trial. Issue 17 (21st April 2015) - Biering-Sørensen, Sofie; Jensen, Kristoffer Jarlov; Aamand, Susanne Havn; Blok, Bastiaan; Andersen, Andreas; Monteiro, Ivan; Netea, Mihai G.; Aaby, Peter; Benn, Christine Stabell; Hasløv, Kaare Robert
Highlights The production of live BCG vaccine is subject to variation in bacterial growth rate. Slow growing BCG was associated with higher frequency of scars and PPD responses. Slow growing BCG was associated with higher cytokine responses in monocytes. Subtle changes in the production of BCG vaccine may influence its immunogenicity.